Atomic force microscopy : a novel tool for the analysis of the mechanism of action of antimicrobial peptides on target membranes - Holroyd, Dale (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.